Clarithromycin Suspension: Bioequivalence Studies on Two Different Strengths - Koytchev, Rossen; Ozalp, Yildiz; Erenmemisoglu, Aydin; Meer, Mike John van der; Alpan, Recep Serdar (Arzneimittelforschung, 2004)
Two studies were performed in different groups of volunteers, with the aim to prove the bioequivalence of test (Klaromin®) and reference clarithromycin (CAS 81103-11-9) suspensions containing in 5 mL either 125 mg (study 1) or 250 mg (study 2) of the drug, administered as an oral dose of 10 mL. Each study was conducted according to an open, randomized, single-dose, two-period cross-over design in healthy volunteers with a wash-out period from 7 to 14 days. Blood samples were taken up to 24 h in both studies, and concentrations of clarithromycin and its principal active 14-hydroxy metabolite were determined by HPLC. In the first study, the 90 % confidence interval for intra-individual ratios of AUC0–t and Cmax of clarithromycin were between 0.84 and 1.03 (AUC0–t) and between 0.89 and 1.03 (Cmax). In the second study, i.e. after administration of clarithromycin suspension 250mg/5mL, the 90 % confidence interval for intra-individual ratios of AUC0–inf and Cmax of clarithromycin were between 1.01 and 1.17 (AUC0–inf) and between 1.01 and 1.16 (Cmax). All these values were within the acceptance ranges for bioequivalence studies. In both studies, the 90 % confidence interval for intra-individual ratios of AUC0–inf and Cmax of 14-hydroxy-clarithromycin were also within the acceptance ranges. In the light of the results of the studies reported here it can be concluded that the clarithromycin test formulations are bioequivalent to the respective reference formulations, i.e. suspensions containing 125 mg/5 mL and 250 mg/5 mL of the drug.
Keywords: CAS 81103-11-9; Clarithromycin, bioequivalence, clinical pharmacokinetics; Klaromin®